"Now we understand what community really means": Reconceptualizing the role of sense of place in the disaster recovery process. (June 2015) - Silver, Amber; Grek-Martin, Jason
Abstract: This study examines the impacts of the F3 tornado that struck the commercial and civic heart of the community of Goderich, Ontario, Canada on 21 August 2011. Using semi-structured interviews (n = 35) and close-ended questionnaires (n = 268), issues relating to sense of place and long-term recovery were explored. Many residents—not merely those directly impacted by the tornado—expressed feelings of loss, worry, and grief as a result of the changes to their familiar landscapes. However, participants also relayed positive outcomes stemming from their shared experiences during and after the disaster, including strong feelings of social cohesion and optimism that persisted well beyond the short-term "honeymoon phase" predicted by the literature. Drawing on and extending recent discussion of "disorientation" and "reorientation" in relation to the disaster-response-recovery experience, this paper contributes to the literature on natural disasters and sense of place. Highlights: Reorientation processes (e.g., restoration, volunteerism) may help to extend the "honeymoon phase" of disaster recovery. Both non-victims and victims can suffer similarly negative psychosocial impacts from disasters. Non-victims may experience feelings of guilt or remorse for receiving fewer damages than friends and neighbours. The restoration of degraded places may be one way to potentially foster the psychosocial healing and growth of disaster survivors.